THEORETICAL AND PRACTICAL PEDAGOGICAL TECHNOLOGIES IN ORGANIZING PHYSICAL EDUCATION LESSONS IN COMPREHENSIVE SCHOOLS (International journal of artificial intelligence, 2025)
This article discusses the theoretical, practical and pedagogical foundations of effective organization of physical education classes in secondary schools. It also analyzes the importance of forming a healthy lifestyle among students, developing physical culture, and using innovative approaches in the lesson process.